2019
DOI: 10.22438/jeb/40/3/mrn-918
|View full text |Cite
|
Sign up to set email alerts
|

Intergeneric grafting for enhanced growth, yield and nutrient acquisition in greenhouse cucumber during winter

Abstract: The objective of the present study was to evaluate the performance (based on growth, yield, quality, and nutrient acquisition) of commercial greenhouse cucumber (Cucumis sativus) grafted onto different locally available species as rootstocks during winter. The performance of cucumber cv. Infinity as scion was tested onto selected genotypes of three species of genus Cucurbita (pumpkin, squash and figleaf gourd), one each of Lagenaria (bottle gourd) and Cucumis (muskmelon) used as rootstocks. Plant growth, fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Specifically, the combination of Nurit rootstock and fruit-thinning was associated with better fruit quality after harvest. It is possible that the Nurit rootstock is more compatible with the 1262 scion (variety) than the TZ rootstock is, as reported for different cucurbitaceous grafted vegetables and in the context of the effects of different rootstock-scion combinations on yield and fruit quality [15,18]. We also found that thinning small fruits a month after fruit-setting had a greater influence on postharvest fruit quality than pruning did.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Specifically, the combination of Nurit rootstock and fruit-thinning was associated with better fruit quality after harvest. It is possible that the Nurit rootstock is more compatible with the 1262 scion (variety) than the TZ rootstock is, as reported for different cucurbitaceous grafted vegetables and in the context of the effects of different rootstock-scion combinations on yield and fruit quality [15,18]. We also found that thinning small fruits a month after fruit-setting had a greater influence on postharvest fruit quality than pruning did.…”
Section: Discussionsupporting
confidence: 66%
“…Pumpkin rootstock is associated with very strong growth vigor, which can promote rapid canopy growth and the rapid growth of lateral stems, and thereby increase the number of fruits on each plant and the total yield [1,15]. However, this may affect the overall fruit quality, as too many fruits that serve as very strong sinks will not develop, ripen and mature in the most optimal way.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found higher dry weight when cucumber grafted onto figleaf gourd than self-grafted plants under salt stress [26]. Similarly, grafting onto figleaf gourd alleviated the declined dry weight of cucumber caused by chilling [27,28] reported stem girth, leaf area, and dry weight were significantly enhanced in figleaf gourd rootstock-grafted than that of non-grafted cucumber plants during winter under unheated greenhouse, subsequently accompanied by 30% yield increase. In the present study, the result also showed that decrease of plant height, stem diameter, leaf area and dry matter contents of cucumber under CA stress was adjusted by grafting onto figleaf gourd (Table 1).…”
Section: Discrepancy Of Morphology and Photosynthesis Between Ng And mentioning
confidence: 76%
“…The development of high yielding cultivars with desirable fruit quality and broad environmental adaptation is crucial for the successful protective cultivation of cherry tomato [4]. Besides, the development of varieties with high yield potential along with resistance to biotic and abiotic stresses constitutes to be an eco-friendly practice [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, introgressing disease-resistant genes in a new variety or hybrid is a time-consuming procedure, and difficult for complex traits such as abiotic stress tolerance [6] Vegetable grafting has proved an efficient substitute tool for classical breeding techniques [7]. It has shown greater potential in boosting the production of several fruiting vegetables, originally under intensive controlled production systems, but its application has been subsequently expanded to non-traditional conditions and fragile agro-ecosystems of arid and semi-arid regions [4,6,8].…”
Section: Introductionmentioning
confidence: 99%